PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA BALAI BESAR METEOROLOGI KLIMATOLOGI DAN GEOFISIKA Wilayah II Tangerang Selatan (BBMKG) - Adinda Putri Amalia; Uswatun Chasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of organizational culture and physical work environment on employee performance at the Center for Meteorology Climatology and Geophysics Region II South Tangerang (BBMKG) this type of research using quantitative methods. Sampling technique using saturated samples and obtained as many as 80 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis test. The results of this study is the organizational culture has a significant effect on employee performance by 40.1% while the remaining 59.9% influenced by other factors. Hypothesis test obtained Value t count > t table or (7.227 > 1.991). Thus Ho1 is rejected and Ha1 is accepted. The physical work environment has a significant effect with a correlation coefficient of 0.647, meaning that both variables have a strong level of relationship. Determination value or influence contribution of 0.416 it can be concluded that the physical work environment variables affect employee performance variables by 41.6% while the remaining 58.4% influenced by other factors. Hypothesis test obtained Value t count > t table or (7.452 > 1.991). Thus Ho2 is rejected and Ha2 is accepted. Organizational culture and physical work environment simultaneously significantly affect employee performance with the regression equation Y = 9.610 + 0,326x1 + 0, 388x2, the coefficient of determination of 46.3% while the remaining 53.7% influenced by other factors that were not conducted research.Hypothesis test obtained Fcounts value > Ftable or 33.256> 3.115. Thus Ho3 is rejected and Ha3 is accepted.